A Study of Copper (II) Schiff Base Ligand Complexes: Characterization and Properties of Copper(II) Schiff Base Ligand Complexes (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The palladium(II), copper(II), cobalt(III) and ruthenium (III) Schiff base complexes with theabove-mentioned ligands (L1-L4), were summarised as dichloromethyl, ethanolbenzene medium, all ofwhich are strong stable, long-term in air, characterised by different physicochemical technologies. Thecomplexes are water insoluble but DMF and DMSO soluble. Yet ethanol and methanol are readily solublein ruthenium and palladium complexes. The experimental evidence on the complex elemental analysis iswell in line with that of the formulation being proposed. The observed molar conductance values areconsistent with the non-electrolytic properties of the preparations except for the Co(III) complexes,which are electrolytes, for all the complexes of 10−3 M DMF solution. By analysing differentphysicochemical techniques, the structures of the prepared complexes are proposed.